BACTERIOLOGICAL (FECAL AND TOTAL COLIFORM) QUALITY OF PAKISTANI COASTAL WATER - Mashiatullah, A.; Javed, T.; Khan, M. S.; Chaudhary, M. Z.; Qureshi, R. M.; Khalid, F. (The Nucleus, 2010)
The coliform bacteria group consists of several genera of bacteria belonging to the family enterobacteriaceae. These are harmless bacteria, mostly live in soil, water, and digestive system of animals. Fecal coliform bacteria, which belongs to this group, are present in large numbers in feces and intestinal tract of human beings and other warmblooded animals which can enter into water bodies from human and animal waste. Swimming in water having high levels of Fecal coliform bacteria increases the chance of developing illness (fever, nausea or stomach cramps) from pathogens entering the body through mouth, nose, ears or cuts in the skin. The objective of the present study was to characterize the bathing quality of Pakistani coastal water with respect to coliform bacteria. Total and Fecal coliform bacteria were determined at seven (7) different locations along Pakistan coast using membrane filtration (MF) technique. 100 ml of water was passed through 0.45 micron (Âµ) filter paper. These filter papers were put on pads, soaked in Lauryle sulphate broth in petri-dishes and incubated at 44o C for Fecal and 37o C for Total coliform for 24 hours. Significantly high population of Fecal and Total coliform bacteria was recorded at Karachi harbour area and Indus delta region. Results indicate that a large amount of domestically originated waste is being discharged into these locations without any pre-treatment (e.g., screening, activated sludge, by using filtration beds etc.) resulting in a poor seawater quality making it unfit for bathing.